2020
DOI: 10.1111/1756-185x.13781
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with depression and anxiety in patients with rheumatoid arthritis: A multicenter prospective cross‐sectional study

Abstract: Aim To investigate the prevalence of and factors associated with depression and anxiety in patients with rheumatoid arthritis (RA). Methods This prospective cross‐sectional study included patients who were consecutively enrolled in the Siriraj Rheumatoid Arthritis Registry or the Thai Army Rheumatoid Arthritis Cohort during the September 2016 to March 2018 study period. Demographic data and clinical variables, including disease activity, functional status, health‐related quality of life, and cognitive function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 22 publications
4
31
0
1
Order By: Relevance
“…Therefore, after adjustment, the effects of other factors associated with anxiety and depression symptoms may be more robust than disease activity. We also found that PtGA (a component of the DAS28-CRP composite measure) was notably associated with anxiety and depression symptom, which is similar to findings from a previous study [37]. Moreover, the multivariable analysis results suggested that inflammation (CRP, TJC, and SJC) was not associated with anxiety and depression.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, after adjustment, the effects of other factors associated with anxiety and depression symptoms may be more robust than disease activity. We also found that PtGA (a component of the DAS28-CRP composite measure) was notably associated with anxiety and depression symptom, which is similar to findings from a previous study [37]. Moreover, the multivariable analysis results suggested that inflammation (CRP, TJC, and SJC) was not associated with anxiety and depression.…”
Section: Discussionsupporting
confidence: 89%
“…2 Despite effective symptom-specific treatments for both seasonal allergic rhinoconjunctivitis and rheumatoid arthritis (RA), levels of non-specific sickness symptoms, including depressed mood, anxiety and fatigue, are high. [3][4][5][6][7][8] Poor subjective sleep is commonly also reported in both conditions. 5,[9][10][11][12][13] The pathophysiology of both allergy and RA involves systemic inflammation, and inflammatory cytokines can be related to sleep disturbances and fatigue and are involved in regulation of sleep.…”
Section: Introductionmentioning
confidence: 98%
“…The psychological effects of RA can be seen in many areas of life such as family life and social relationships, therefore, it can lead to mood disorders (5). These mood disorders can cause pain, increased disease activity, cytokine release, immune-modulatory responses, and sleep disorders in patients.…”
Section: Introductionmentioning
confidence: 99%